Formation and Promotion of the Territory Brand as an Instrument of Its Development on the Example of the Arkhangelsk Oblast - Kristina V. Zavetskas; Marina V. Minina (Арктика и Север, 2025)
Territorial development is aimed at identifying and actively using resources, opportunities, and socio-economic potential to improve the quality of life of the population, increase attractiveness among investors, tourists, and representatives of economically active social groups. The complexity of territorial development is that it is necessary to take into account a large number of external factors, such as the political and economic situation in the country and the world, socio-demographic processes, the spread of modern information technologies, and much more. It is impossible to ignore the internal characteristics of the territory: its history, natural and climatic features, level of urbanization, resource potential, dynamics of social processes, etc. The diversity of relationships and contradictions between the external and internal environment of the territory complicates the process of territorial development. To overcome these contradictions, it is necessary to form a holistic image or brand of the territory aimed at the most complete and effective use of the resource potential. This article considers the process of formation and promotion of the territory brand as a tool for its development. The problems hindering the effective branding of the territory have been identified. The SWOT-analysis of the Arkhangelsk Oblast is carried out on the basis of the generalization of statistical data characterizing the socio-economic situation of the region. Proposals aimed at overcoming the problems of territorial brand development, related to the implementation of a targeted program of public involvement in the formation of an attractive image of the region, are developed.